TESTIMONIUM DE AUDITU PROOF IN CONFIRMATION OF MARRIAGE DECISION (ISBAT NIKAH) (Normative Studies to the Decision Number 69/PDT.P/2012/PA.MLG) - Ayu Tunjung Wulandari (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2013)
ABSTRACTAYU TUNJUNG WULANDARI, Civil Law, Faculty of Law, University of Brawijaya, Testimonium De Auditu Proof In confirmation of Marriage Decision (Isbat Nikah) (Normative Studies to The Decision Number 69/Pdt.P/PA.Mlg), Supervisor: Ulfa Azizah, SH, M.Kn. and M. Hisham Syafioedin, S.H; 19 pages.In this paper the author discusses the issue of proof testimonium de auditu in request of ‘isbat nikah’ In Article 171 HIR de auditu mentioned that testimony can not be accepted as valid evidence. According to some legal experts testimony de auditu not allowed because such information does not relate to events experienced by themselves, so the witness de auditu not constitute evidence and need not be considered. However, the determination of the request confirmation of ‘isbat nikah’ Number: 69/Pdt.P /2012/PA.Mlg, judge accepted the testimony of de auditu as valid evidence through several considerations. This study aims to identify and analyze the determination of ‘isbat nikah’ request Number: 69/Pdt.P/2012/PA.Mlg about proving testimonium de auditu. Thus it can be seen why the Malang religious court judge granted the applicant.This research is a normative juridical approach to the legislation. Therefore this study used type of primary legal materials, secondary, and tertiary obtained from the study of literature. Analytical techniques used in this research is descriptive qualitative techniques. Based on the results of the study, the authors obtained answers to existingproblems. Malang Religious Court judges grant applicants with some considerations on the basis of the applicant's conduct and the confirmation of marriage just to take care of a retired widow. And keep in mind that there are three purposes of the law, justice, expediency, and certainty. In this case Judge emphasizes expediency than other legal purposes, and also for the benefit of the applicant. The conclusion of this study was largely a general provision of Article 171 HIR is not binding and can be ruled out by considering the extent to which the quality and probative value of the testimony given by the witness de auditu. Researchers suggested that in solving this problem of legal practitioners should not be fixated on formal rules, neglecting the rules of law in society, the rules of religion in other words that the underlying judgment the judge in determining the application for confirmation of marriage is for the benefit of the applicant.Key word: testimonium de auditu, isbat nikah